EFFECT OF A THEMATIC APPROACH ON THE CONCEPTIONS OF CIGARETTE AND PASSIVE SMOKING IN CHILDREN OF THE SECOND YEAR OF ELEMENTARY SCHOOL FROM TWO MUNICIPAL SCHOOLS OF GUARAPUAVA-PR - Lima, Ana de Souza; Faustino, Larissa de Lima; Souza, Matheus Rodrigues de; Bonini, Juliana Sartori; Bonini, Juliana Sartori; Meira Martins, Leo Anderson (Cadernos de Educação Tecnologia e Sociedade, 2019)
Smoking is considered to be a chronic disease caused by the nicotine dependence. The passive smoking is the leading cause of childhood respiratory disease. This research aimed to evaluate the conceptions that 2nd year-students of the Elementary School of two public schools at Guarapuava-PR, aging between 6 and 8 years, have about cigarettes and passive smoking. The work was performed at three moments: (1) without a preliminary intervention, the students answered a semi-structured questionnaire composed of 5 questions on cigarette and passive smoking (Pre-test, PT); (2) the students participated of activities where they saw an educational video and read a comic book whose theme dealt with the influence of the cigarette and the physiology of the respiratory system; (3) after 1 week and after 1 month, the students answered the same questionnaire offered in the PT (called respectively post-test 1 week, PTS, and post-test 1 month, PTM). More than 50% of students said they live with smokers at home. Children who answered did not know the cigarette answered otherwise following the thematic approaches. Children who answered to stay close to smokers answered otherwise following the thematic approaches. More than 60% of students answered that teacher do not address the cigarettes and passive smoking topic in the classroom, but they changed their responses after the thematic approach. The conceptions of children relating cigarette use to lung damage increased. This study showed that the approaches taken at schools with children who study in the initial grades of elementary school were effective.